2006
DOI: 10.2174/157339906775473572
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Triamcinolone for the Treatment of Diabetic Macular Edema

Abstract: Diabetic macular edema is one of the leading causes of visual loss in first world countries and the first cause in diabetic retinopathy. The Early Treatment Diabetic Retinopathy Study showed a significant benefit in using focal laser photocoagulation for the treatment of macular edema, more specifically defined as clinically significant macular edema. Nevertheless, progressive visual loss is found in the 26% of patients with diabetic macular edema treated with photocoagulation. The failure of laser treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 67 publications
0
9
0
8
Order By: Relevance
“…triamcinolone acetonide alone. [26][27][28] However, the i.v.t. triamcinolone acetonide injection is not without potential risks, including transient rise in IOP, cataract progression, vitreous hemorrhage, retinal detachment, sterile pseudoendophthalmitis of uncertain etiology, as well as endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
“…triamcinolone acetonide alone. [26][27][28] However, the i.v.t. triamcinolone acetonide injection is not without potential risks, including transient rise in IOP, cataract progression, vitreous hemorrhage, retinal detachment, sterile pseudoendophthalmitis of uncertain etiology, as well as endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is evidence that these inflammatory-like processes contribute to the pathogenesis of DR in both animal and patient studies, in that inhibition of proinflammatory enzymes or deletion of such enzymes inhibits diabetes-induced vascular pathology in animal models of DR. 32 Studies also have shown that leukocytes play an important role in the structural and functional abnormalities that characterize DR. 33,34 In patients, the most compelling evidence that inflammatory processes play an important role in DR pathogenesis is the dramatic effect of corticosteroids on DME. 7,35 Therefore, the specific cell types that mediate these proinflammatory effects are of great interest.…”
Section: Inflammation and Diabetic Retinopathymentioning
confidence: 99%
“…Poslednja suptenonska primena triamcinolon-acetonida nije praćena značajnim porastom IOP, te predstavlja efikasan i relativno Ključne reči: dijabetesna makulopatija, oštrina vida, centralna makularna debljina, intraokularni pritisak pseudohipopiona (12). Triamcinolon-acetonid (TA) je kortikosteroid koji u visokim lokalnim koncentracijama u zadnjem segmentu oka ispoljava antiinflamatorni, angiostatički efekat i smanjuje ekstravazaciju tečnosti (13,14). Cilj rada je procena efikasnosti i sigurnosti (merenjem IOP, centralne makularne debljine i oštrine vida pre i nakon dva meseca) poslednje suptenonske injekcije kortikosteroida TA u lečenju dijabetesne makulopatije.…”
Section: Uvodunclassified